Marginalizm w literaturze - Irina Titova (Postscriptum Polonistyczne)
The author of the article tries to use margin as a category in the history of literature. She concentrates on those writers whose works can be regarded as existing on the margins (Villon, de Sade) or those whose works feature people living „on the margins” of society. Writers often portrayed people who lived on the edge of society (Villon, Hugo, Genet), those who were rejected by society because of their individual features (Simplicyssimus, Guliwer), or those with clear philosophical ideas that were aimed at social norms and tradition (the heroes of de Sade, Rimbaud, Turgieniev). Some of these people decided to leave society to exist on its margins, use alcohol and drugs, feel alienated and unable to find their own place in the world (heroes of de Quincey, Bułhakov, Hesse).